Assessment Criteria in Academic Writing in English: Rater Sessions and reliability - Salinas, Julieta (2021)
The assessment of foreign language writing is a complex and manifold process, which entails that this field of research be approached from different perspectives. This paper arises from the need to research the teaching criteria when assessing writing in a foreign language (English) in a university context. This research is part of a larger biannual research project called «Criteria for the assessment of foreign language (English) writing at the higher level» (supported by the Secretariat of Science and Technology of the National University of Córdoba, Argentina). In this particular work, we will analyze the data collected in a meeting at which nine teachers explained how they scored five written essays under summative assessment. We believe that this analysis will foster reflection on the selection, weighting and uniformity of assessment criteria to be applied in the future.